Dinamika Psikologis Pembelajaran Blended Learning - Alucyana, Alucyana (Journal of Islamic and Contemporary Psychology, 2021)
The Covid-19 pandemic has changed many lines of life, both economic, social and educational. The economic sector suffered massive losses. Several transportation companies were forced to ground their fleets due to this pandemic. In the social sector, there are also social restrictions. The government appeals to the public to limit activities outside the home with the aim of breaking the chain of the spread of Covid 19. Another sector that has also been affected by the Covid-19 Pandemic is the world of Education. Distance learning with an online system must be done so that learning continues. One of the learning models used in distance learning is Blended Learning. This learning is considered effective to adjust in this Pandemic period. Even though it is indicated, even though this Pandemic disaster is over, the Blended Learning learning model can still be used, given the increasingly rapid development of technology. It's just that the implementation of the blended learning learning model also leaves problems to be solved. Psychological dynamics occur for teachers, parents and students. The teacher becomes worried whether the learning that the teacher conveys has reached the target for the students. Parents also become anxious, because they are limited in using technology and have to accompany their children while studying. Students also become bored because they have to use electronic media such as cellphones, computers and others every day. This article aims to describe theoretically about Psychological Dynamics in Blended Learning.